A possible role for miRNA silencing in disease phenotype variation in Swedish transthyretin V30M carriers - Olsson Malin; Norgren Nina; Obayashi Konen; Plante-Bordeneuve Violaine; Suhr Ole B; Cederquist Kristina; Jonasson Jenni (BMC, 2010)
Abstract Background Familial amyloidosis with polyneuropathy (FAP) is an autosomal dominant disease caused by transthyretin (TTR) mutations, of which V30M (TTR c.148G > A, p.Val50Met, "Val30Met") is the most common. Swedish V30M carriers display later age at onset and lower penetrance compared to other populations. Methods In the study, 130 Swedish V30M carriers (32 early, 30 late onset and 68 asymptomatic carriers) and 50 controls, 23 French symptomatic V30M carriers and 29 controls and 18 Japanese symptomatic V30M carriers and 29 controls were included. We aimed to identify additional genetic factors in the TTR gene and its surrounding region that could have an impact on phenotype. Results We identified three SNPs (rs71383038, rs3794885 and rs62093482) with a significant difference in allele frequency between Swedish V30M carriers and controls. The two Swedish V30M homozygous patients present in the study also displayed homozygosity for the CA10 (rs71383038), A (rs3794885) and T (rs62093482) alleles in these SNPs. Hence, these alleles are present on the Swedish V30M haplotype. Of these, rs62093482 is located in the 3'UTR of TTR gene and thus more interesting since SNPs in the 3'UTR can affect gene expression levels by modifying microRNA (miRNA) targeting activity. miRNA target predictions revealed four potential miRNAs with predicted targets unique for the polymorphic allele. Conclusions Our results are the first to show the presence of a 3'UTR polymorphism on the V30M haplotype in Swedish carriers, which can serve as a miRNA binding site potentially leading to down-regulated expression from the mutated TTR allele. This finding may be related to the low penetrance and high age at onset of the disease observed in the Swedish patient population.